93.3k views
1 vote
10-5x=3(x-4)-2(x+7)-------

2 Answers

3 votes

Answer:

x=6

Explanation:

10-5x=3(x-4)-2(x+7)

Distribute

10-5x=3x-12-2x14

Combine like terms

10-5x = x-26

add 5x to each side

10-5x+5x = x+5x-26

10 = 6x-26

Add 26 to each side

10+26 = 6x-26+26

36 = 6x

Divide by 6

36/6 = 6x/6

6 =x

User Hoha
by
6.0k points
5 votes

Answer:


10-5x=3\left(x-4\right)-2\left(x+7\right)


3\left(x-4\right)-2\left(x+7\right)

combine like terms:-


=3x-12-2x-14


3x-2x=x


=x-12-14

Subtract -12 -14


=x-26


10-5x=x-26

Subtract 10 from both sides:-


-5x=x-36

Now, subtract x from both sides:-


-5x-x=x-36-x


-6x=-36

Divide both sides by -6:-


(-6x)/(-6)=(-36)/(-6)


x=6

OAmalOHopeO

User Shambo
by
4.9k points